Anti-dandruff efficacy of ayurvedic scalp leave-on treatment: a double-blinded, randomized placebo-controlled clinical study - Madhavi, Machavolu Soubhagya Lakshmi; Shukla, Ravi Kant; Gudulkar, Susmita; Mathur, Saurabh; Punyani, Supriya (International Journal of Research in Dermatology, 2025)
Background: This study aimed to evaluate the efficacy and safety of ayurvedic leave on treatment product in the management of dandruff through a randomized, double-blind, placebo-controlled study. Methods: A total of 112 subjects with clinically diagnosed moderate dandruff were randomly assigned to group A (ayurvedic leave-on treatment group) and group B (placebo group), where 110 subjects completed the study. The treatment phase was for 4 weeks, followed by a regression phase of 1 week. Subjects applied the allotted product on their scalp and massaged. It’s a leave on product so the subjects were asked not to wash off. Results: After 4 weeks of treatment, test product group A demonstrated a significantly greater reduction in dandruff severity compared to group B (p<0.05). The adherent dandruff scores in group A showed a significant reduction of 17.56 units/41% while in group B, it was noted to be 29.4%/12.4 units. Additionally, 100% of subjects in group A reported a subjective perception improvement in symptoms of dandruff within 2 weeks when compared to group B which is only by 81%. Conclusions: Indulekha Svetakutaja scalp leave-on treatment is a safe and highly effective solution designed to combat dandruff while simultaneously enhancing the overall health of the scalp and hair.